Differential impairment of lytic and cytokine functions in senescent human immunodeficiency virus type 1-specific cytotoxic T lymphocytes - Dagarag, Mirabelle; Ng, Hwee; Lubong, Rachel; Effros, Rita B; Yang, Otto O (Journal of virology, 2003)
Telomere length is abnormally short in the CD8(+) T-cell compartment of human immunodeficiency virus type 1 (HIV-1)-infected persons, likely because of chronic cell turnover. Although clonal exhaustion of CD8(+) cytotoxic T lymphocytes (CTL) has been proposed as a mechanism for loss of antigen-specific responses, the functional consequences of exhaustion are poorly understood. Here we used telomerase transduction to evaluate the impact of senescence on CTL effector functions. Constitutive expression of telomerase in an HIV-1-specific CTL clone results in enhanced proliferative capacity, in agreement with prior studies of other human cell types. Whereas the CTL remain phenotypically normal in terms of antigenic specificity and requirements for proliferation, their cytolytic and antiviral capabilities are superior to those of control CTL. In contrast, their ability to produce gamma interferon and RANTES is essentially unchanged. The selective enhancement of cytolytic function in memory CTL by ectopic telomerase expression implies that loss of this function (but not cytokine production) is a specific consequence of replicative senescence. These data suggest a unifying mechanism for the in vivo observations that telomere lengths are shortened in the CD8(+) cells of HIV-1-infected persons and that HIV-1-specific CTL are deficient in perforin. Telomerase transduction could therefore be a tool with which to explore a potential therapeutic approach to an important pathophysiologic process of immune dysfunction in chronic viral infection.